Tailoring restoration interventions to the grassland‐savanna‐forest complex in central Brazil. Issue 5 (27th June 2019) - Schmidt, Isabel B.; Ferreira, Maxmiller C.; Sampaio, Alexandre B.; Walter, Bruno M. T.; Vieira, Daniel L. M.; Holl, Karen D.
Abstract : Defining the reference system for restoration projects in regions characterized by complex vegetation mosaics is challenging. Here we use the Cerrado region of Brazil as an example of the importance of clearly defining multiple natural and anthropogenically altered states in grassland‐savanna‐forest mosaics. We define three main, natural vegetation types–grassland, savanna, and scleromorphic ( cerradão ) forest–to (1) distinguish between original and degraded states and (2) set appropriate targets for and guide restoration. We contend that the differences in Cerrado vegetation composition originally were driven by soil conditions and secondarily by fire frequency and precipitation patterns that differ from the core to the edge of the Cerrado region. Grasslands are found on the shallowest, least fertile soils and/or in waterlogged soils; scleromorphic forests are generally located on deeper, more fertile soils; and savannas occupy an intermediate position. In recent decades, this biophysical template has been overlain by a range of human land‐use intensities that strongly affect resilience, resulting in alternative anthropogenic states. For example, areas that were originally scleromorphic forest are likely to regenerate naturally following low‐ or medium‐intensity land use due to extensive resprouting of woody plants, whereas grassland restoration requires reintroduction of grass and forb species that do not tolerate soil disturbance and exotic grass competition. Planting trees into historic grasslands results in inappropriate restoration targets and often restoration failure. Correctly identifying original vegetation types is critical to most effectively allocate scarce restoration funding.